Investigation of Solute Diffusion through Polyvinyl Alcohol/ Polyallylamine Ultrafiltration Membrane - D Ariono; A K Wardani; P T P Aryanti; I G Wenten (ASEAN Journal of Chemical Engineering, 2019)
Ultrafiltration membrane has been widely used for several applications due to their high separation capacity, high selectivity, and low operating pressure. In this work, solutes diffusion through polyvinyl alcohol/polyallylamine ultrafiltration membrane was investigated. The membrane was prepared by phase inversion method with glutaraldehyde as crosslinking agent. Meanwhile, NaCl and CaCl2 were used as solutes, either as a single or double solute. The results showed that the increase of polyallylamine concentration led to the increase of membrane swelling degree. For both single and double solutes, diffusion of Na+ and Ca2+ were slightly decreased with the increase of swelling degree. However in double solute diffusion, there was interaction between Na+, Ca2+, and membrane that made Na+ ions moved faster and Ca2+ ions moved slower compared to single solute diffusion. In addition, the increase of solute concentration led to the increase of Na+ diffusion coefficient and the decrease of Ca2+ diffusion coefficient.